What can Cambodia learn from Thailand and India as it prepares to graduate from Least Developed Country status? - Brigitte Tenni; Deborah Gleeson; Joel Lexchin; Phin Sovath; Chalermsak Kittitrakul (South Centre, 2024)
Cambodia is expected to graduate from Least Developed Country status soon, at which time it will be required to make patents available for pharmaceutical products and processes to meet its obligations under the Agreement on Trade Related Aspects of Intellectual Property Rights (TRIPS). Given its impending transition from LDC status, there is a need to balance Cambodia's intellectual property (IP) policies and regulations with public health priorities to ensure access to affordable life-saving medicines. This will be critical to achieving universal health coverage, one of the United Nations' Sustainable Development Goals. This paper examines Cambodia's IP laws and regulations to identify provisions that could reduce access to affordable generic medicines when it starts granting patents for pharmaceuticals. It systematically compares Cambodia's IP laws and regulations with those of Thailand and India - two developing countries that have had some successes in preserving access to medicines despite the introduction of pharmaceutical patents. It identifies lessons for Cambodia from the experiences of Thailand and India in implementing TRIPS and using TRIPS flexibilities such as compulsory licensing to ensure access to a sustainable supply of affordable generic medicines. Key recommendations for reform for Cambodia include strengthening the use of preventive and remedial TRIPS flexibilities and removing criminal sanctions for patent infringements. Cambodia should reject any TRIPS-plus provisions in its patent legislation and avoid membership in bilateral or plurilateral trade agreements that include TRIPS-plus provisions as well as signing patent treaties and memorandums of understanding that may facilitate the granting of unwarranted patents.
Keywords: 300; Access to Medicines; Affordable Medicines; Bolar; Cambodia; Compulsory Licenses; Compulsory Licensing; European Union (EU); Flexibilities; Generic Medicines; India; Intellectual Property; LDC Graduation; LDC Transition Period; Patent; Patent Law; Pharmaceuticals; Public Health; Thailand; TRIPS; TRIPS Agreement; TRIPS Flexibilities; TRIPS Plus; TRIPS-Plus Provisions; Universal Health Coverage (UHC)